Reforms for a Cleaner, Healthier Environment in China - Hill, Sam (OECD Economics Department Working Papers, 2013)
China's exceptional economic expansion has led to rising energy demand and pollution as well as other environmental pressures. Strong efforts by the government have moderated emissions of some types of air and water pollution from high levels but others, including greenhouse gas emissions, continue to rise. Poor air and water quality threaten human health, create other costs and reduce well-being. The 12th Five Year Plan aims at further reducing pollution and at other environmental improvements. To achieve these goals in a cost-effective manner wide-ranging reforms are needed. Reliance on command-and-control measures ought to make way gradually for well-implemented market-based approaches. Energy and water pricing need to be reformed to provide stronger incentives for end-users. So does pollution pricing. A carbon tax should be given serious consideration, especially if pilot carbon emissions trading schemes turn out to be difficult to implement. As well, stronger standards are needed, including for motor vehicles and fuels. Efforts to enhance environmental enforcement, particularly at the local level, will also be key to further progress. This Working Paper relates to the 2013 OECD Economic Survey of China (www.oecd.org/eco/surveys/china)